Fungi Associated With Acid Lime Damping Off In Nursery Conditions (Journal of Plant Disease Sciences, 2023)
Investigation on the fungi associated with acid lime damping off in nursery conditions undertaken to know the fungi associated with acid lime damping off. Typical specimen of damping off disease sample was collected from acid lime nursery of AICRP on Fruits scheme. Dr. PDKV, Akola and brought to the laboratory. The associated pathogens were isolated using the hyphal tip method and pathogenicity of these pathogens was successfully demonstrated in pot culture. The pathogens were identified as Fusarium solani, Rhizoctonia bataticola, Sclerotium rolfsii and Pythium spp. based on symptomology, cultural, morphological characteristics observations and the pathogenicity test.
Keywords: Acid lime; Damping off; Fungi associated